2018
DOI: 10.1016/j.molcel.2018.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Lamins Organize the Global Three-Dimensional Genome from the Nuclear Periphery

Abstract: Lamins are structural components of the nuclear lamina (NL) that regulate genome organization and gene expression, but the mechanism remains unclear. Using Hi-C, we show that lamins maintain proper interactions among the topologically associated chromatin domains (TADs) but not their overall architecture. Combining Hi-C with fluorescence in situ hybridization (FISH) and analyses of lamina-associated domains (LADs), we reveal that lamin loss causes expansion or detachment of specific LADs in mouse ESCs. The det… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
160
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 182 publications
(183 citation statements)
references
References 58 publications
22
160
1
Order By: Relevance
“…Lamins are known to influence the expression of genes found both in the lamina‐associated chromatin domains (LADs) and in the non‐LADs. Our recent studies of lamin null mouse embryonic stem cells (mESCs) have shown that lamins regulate the 3D chromatin organization by ensuring the proper condensation and position of LADs at the nuclear periphery (Zheng et al, ). The de‐condensation and detachment of LADs upon lamin loss can lead to altered gene expression by bringing the active chromatin domains into the close vicinity of inactive ones.…”
Section: Discussionmentioning
confidence: 99%
“…Lamins are known to influence the expression of genes found both in the lamina‐associated chromatin domains (LADs) and in the non‐LADs. Our recent studies of lamin null mouse embryonic stem cells (mESCs) have shown that lamins regulate the 3D chromatin organization by ensuring the proper condensation and position of LADs at the nuclear periphery (Zheng et al, ). The de‐condensation and detachment of LADs upon lamin loss can lead to altered gene expression by bringing the active chromatin domains into the close vicinity of inactive ones.…”
Section: Discussionmentioning
confidence: 99%
“…Various models of lamin association with LADs have been proposed, including direct tethering to chromatin domains ( Gonzalez-Sandoval et al 2015) and a 'meshwork caging model' where the dense lamin network traps chromatin domains (Amendola and Steensel 2015;Kim, Zheng, and Zheng 2019). Work in Lamin null (Lamin B1, B1 and A triple knockout) mice demonstrated that loss of LADs altered chromatin organisation and affected gene expression in neighbouring 'non-LAD' genomic regions (Zheng et al 2018). Interestingly, murine skin develops normally without Lamin B1 or B2 expression (Yang et al 2011) and…”
Section: Discussionmentioning
confidence: 99%
“…The authors proposed that the role of lamin in LADs might be dependent on the cell type and that other components of the nuclear lamina might help to organize LADs (Amendola & Steensel, 2015). However, a more recent study reported decondensation or detachment of specific LAD regions from the nuclear periphery in lamin null mouse ESCs, which alters the chromatin domain interactions and transcription (Zheng et al, 2018). Additional studies indicated that lamins are essential for chromatin organization at early developmental stages (Melcer et al, 2012).…”
Section: Chromatin Organizationmentioning
confidence: 99%